2014
DOI: 10.1177/2050640614531574
|View full text |Cite
|
Sign up to set email alerts
|

Prediction scores or gastroenterologists’ Gut Feeling for triaging patients that present with acute upper gastrointestinal bleeding

Abstract: Gut Feeling is an independent predictor for the need of a clinical intervention, rebleeding, and mortality in patients presenting with upper GI bleeding; however, the Blatchford and Rockall scores are stronger predictors for these outcomes. Combining Gut Feeling with the Blatchford and Rockall scores resulted in the most optimal prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
4
14
0
1
Order By: Relevance
“…As regards age, this study showed that, the mean age of studied patients was 56.92 ± 11.54 years. This is similar to results of De Groot et al, who evaluated value of prediction scores in patients with suspected upper gastrointestinal bleeding, and found that the mean age of the studied patients was 65 (range 18 -99) [11]. and that 63% of their studied patients were males too.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As regards age, this study showed that, the mean age of studied patients was 56.92 ± 11.54 years. This is similar to results of De Groot et al, who evaluated value of prediction scores in patients with suspected upper gastrointestinal bleeding, and found that the mean age of the studied patients was 65 (range 18 -99) [11]. and that 63% of their studied patients were males too.…”
Section: Discussionsupporting
confidence: 90%
“…Twenty percent of patients in this study were shocked during presentation and this finding is similar to a study conducted by Gado et al [16] who stated that (18%) were shocked during presentation. Blood transfusion was required to (58%) of patients in the current study and this also similar to the study of De Groot et al [11] who stated that blood transfusion was required for (58%) of patients and supported with Morsy et al [13] who stated in their study that blood transfusion was required for (61%) of patients.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the fact that use of risk scores in management of UGIB is recommended in several studies and guidelines [2,13,14], its role in actual clinical decisions and hospital guidelines is still unclear [17]. Although, some studies proved that risk scores are a stronger predictor than clinical decision, others believe the opposite [2,18,19]. This controversy may originate from variations in hospital characteristic; however, in our hospital, as patients are initially assessed by junior doctors, using risk scores seems to be preferred approach.…”
Section: Discussionmentioning
confidence: 99%
“…Following the introduction of these systems, numerous studies have been conducted to validate them [2] and the discrepancy in results led to the idea that variation in geographical region and health care system affects the accuracy of risk scores [17][18][19]. Although, many guidelines suggest that low risk patients can be managed as outpatient, In our hospital all patients with UGIB undergo endoscopy and the timing is mostly within the first 24 hours of admission [14,20].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent multicentre study, although clinical knowledge of the endoscopists (described as "gut feeling") was an independent predictor for an adverse outcome, it had a lower sensitivity and a worst predictive power compared to prediction scores [77] . The reasons for not using clinical scores may be that they are difficult to calculate and time consuming and do not add much information to the physician's knowledge.…”
Section: Therapeutic Decisions -Why or Why Not Should We Use A Risk Smentioning
confidence: 99%